La experiencia del retiro en deportistas de alta competencia en Lima - Mendoza Llontop, Paola Sofia (2019)
The investigation seeks to know about the retirement experience of elite athletes, in Lima, Peru. This study was developed under a qualitative, exploratory and descriptive approach, using a phenomenological methodology. To gather information, it was used an entry data forms and semi-structured interviews with the ten participants. The categories that allowed the analysis of information were: the sport personal meaning, retirement causes, personal meaning of retreat, retirement reaction, retreat impact, adaptation resources and current satisfaction. The results revealed that each participant experienced the retreat in a unique way, generating, mostly, a negative impact on the life of the athlete. However, during the adaptation process there were personal and social resources that helped the athlete to face successfully this difficult stage.